Chemsex and the city: sexualised substance use in gay bisexual and other men who have sex with men attending sexual health clinics. (March 2017) - Hegazi, A; Lee, MJ; Whittaker, W; Green, S; Simms, R; Cutts, R; Nagington, M; Nathan, B; Pakianathan, MR
The objective of this study was to analyse associations between sexualised substance use (chemsex), STI diagnoses and sexual behaviour among gay bisexual and other men who have sex with men accessing sexual health clinics to better inform clinical pathways. A retrospective case notes review was undertaken following the introduction of more detailed and holistic profomas for all gay bisexual and other men who have sex with men attending two London sexual health clinics between 1 June 2014 and 31 January 2015. Chemsex status was documented for 655/818. Overall, 30% disclosed recreational drug use of whom 113 (57%) disclosed chemsex and 27 (13.5%) injecting drugs. HIV-positive gay bisexual and other men who have sex with men were more likely to disclose chemsex (AOR 6.68; 95% CI 3.91–11.42; p < 0.001). Those disclosing chemsex had a higher incidence of acute bacterial STIs (AOR 2.83 CI 1.79–4.47; p < 0.001), rectal STIs (AOR 3.10 CI 1.81–5.32; p < 0.001) or hepatitis C (AOR 15.41 CI 1.50–158.17; p = 0.021). HIV incidence in the study period was 1.8% (chemsex) vs. 0.9% (no chemsex) (p = 0.61). Chemsex was associated with having more sexual partners, transactional sex, group sex, fisting, sharing sex toys, injecting drug use, higher alcohol consumption and the use of 'bareback' sexual networking applications (p < 0.004). Chemsex participants were also more likely to have accessed post-exposure prophylaxis for HIV in the study period and report sex with a discordant HIV or hepatitis C-infected partner (p < 0.001). Chemsex disclosure is associated with higher risk-taking behaviours, acute bacterial STIs, rectal STIs and hepatitis C incidence. HIV incidence was higher but not significantly so in the study period. Chemsex disclosure in sexual health clinics should prompt an opportunity for prevention, health promotion and wellbeing interventions.